Dying to be thin - McPhee, Larkin; Sarandon, Susan, 1946-; Twin Cities Public Television (Saint Paul, Minn.); WGBH (Television station : Boston, Mass.); WGBH Video (Firm) ([Boston] : WGBH Video, 2004)
Documentary on anorexia nervosa and bulimia, eating disorders that have grown increasingly prevalent in contemporary American society. Experts in the field discuss some of their underlying causes (especially cultural pressures to be thin), their physiological and psychological effects, and some medical and therapeutic treatments that have been developed. The interviewees include patients representing particularly vulnerable groups: young women from troubled families, dancers, fashion models, and athletes.
DVD, region 1, full screen presentation; Dolby Digital.
Closed-captioned.
Videodisc release of a 2000 television production.
Editor, Steve Fischer ; camera, Robert Hutchings, Michael Phillips ; music, Michael Bacon ; narrated by Susan Sarandon.
MPAA rating: Not rated.
YALSA selected video for young adults 2002.
Keywords: Eating disorders -- United States; Anorexia nervosa; Bulimia; Body image in women; Body image in adolescence; Body image disturbance; Documentary television programs; Nonfiction television programs; Video recordings for the hearing impaired